KEBIJAKAN FORMULASI SANKSI KEBIRI KIMIA DI INDONESIA DI TINJAU DARI PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2016 TENTANG PERLINDUNGAN ANAK - Endik Wahyudi; Gerry Gerry Joe (universitas islam darul ulum lamongan, 2019)
The crime of sexual violence in Indonesia is increasing every year. Criminal penalties for perpetrators of sexual violence as stated in the Penal Code and Child Protection Act were considered ineffective until the Government issued The Replacement Government Regulation No. 1 of 2016 that applies criminal sanctions to perpetrators of sexual violence among others by chemically applying castration. This is the background to conducting normative research on the policy of chemicalbirth sanction formulations that apply in Indonesia today. His arrangement of chemical castration and rehabilitation as an additional punishment, to date has not been published, so the mechanisms and technicalities are unknown. In addition, interested sectors are not involved in the establishment of such rules resulting in rejection as executors.